2016
DOI: 10.5194/isprs-archives-xli-b8-265-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evaluation of Nocturnal Cold Air Drainage Over a Simple Slope Using Thermal Infrared Imagery

Abstract: ABSTRACT:Measurements of climatic processes such as cold air drainage flows are problematic over mountainous areas. Observation of cold air drainage is not available in the existing observation network and it requires a special methodology. The main objective of this study was to characterize the cold air drainage over regions with a slope. A high resolution infrared camera, a meteorological station and Digital Elevation Model (DEM) were used. The specific objective was to derive nocturnal cold air drainage ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In further studies, flow velocity, cold air production rates, and cold air volume should be measured or calculated with the aid of model simulations. A simple method for estimating mean wind velocity is provided in the [12]. They combined data from a digital elevation model with data from a meteorological station and TIR images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies, flow velocity, cold air production rates, and cold air volume should be measured or calculated with the aid of model simulations. A simple method for estimating mean wind velocity is provided in the [12]. They combined data from a digital elevation model with data from a meteorological station and TIR images.…”
Section: Discussionmentioning
confidence: 99%
“…According to [10], 5 K lower air temperatures or more can be measured in such cold air pools compared to the outside of the cold air pool. The generation and drainage of cold air on mountain slopes [11,12] and on low-roughness opened and greened spaces [13] and its benefits for surrounding urban areas has already been investigated by [14]. They demonstrated that with high-relief energy, there is cold air runoff, and the cold air can penetrate into urban structures and contribute to local cooling.…”
Section: Introductionmentioning
confidence: 99%